FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PEMILIHAN KARIR MAHASISWA AKUNTANSI SEBAGAI AUDITOR PEMERINTAH (STUDI EMPIRIS MAHASISWA UNRI) - Tarigan, Muhammad Ilyas; Azlina, Nur; Silfi, Alfiati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The objective of this study to examine the influence of Motivation Market, Economic Motivation, Work Environment, Individual Personality, Professional Training and Professional Recognition for Career Selection of Student Accounting toward Government Auditor . The questionnaire was used as instrument of this study which was distributed a total of 319 copies to Riau University Students of 2010 and 2011 Period who was taken concentration major and have proposed the proposal. The data collected were analyzed using multiple regression analysis version 18.0. The result of this study proved that Influence of Motivation Market, Economic Motivation, Work Environment, Individual Personality, Professional Training and Professional Recognition has signifiant influenced toward Career Selection of Student Accounting to have been Government Auditors as multiple correlation coefficient (R) of 0.618 and a strong relationshipKeywords: Motivation Market, Economic Motivation, Work Environment, Individual Personality & Professional Training.